If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -6 + y + 36 = 8y + 30 + -6y Reorder the terms: -6 + 36 + 3y + y = 8y + 30 + -6y Combine like terms: -6 + 36 = 30 30 + 3y + y = 8y + 30 + -6y Combine like terms: 3y + y = 4y 30 + 4y = 8y + 30 + -6y Reorder the terms: 30 + 4y = 30 + 8y + -6y Combine like terms: 8y + -6y = 2y 30 + 4y = 30 + 2y Add '-30' to each side of the equation. 30 + -30 + 4y = 30 + -30 + 2y Combine like terms: 30 + -30 = 0 0 + 4y = 30 + -30 + 2y 4y = 30 + -30 + 2y Combine like terms: 30 + -30 = 0 4y = 0 + 2y 4y = 2y Solving 4y = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 4y + -2y = 2y + -2y Combine like terms: 4y + -2y = 2y 2y = 2y + -2y Combine like terms: 2y + -2y = 0 2y = 0 Divide each side by '2'. y = 0 Simplifying y = 0
| -8(x+5)-7=-6(x-1) | | 4y=34.8 | | -28+5k=k-3k | | 9z-8z=58-50 | | 4y=(-3-y)+8 | | 9=-3(6+a) | | 3(8+r)=30 | | 5c+5c=-20 | | 2u+4=-18 | | Cosx=6-2 | | 6a-4y-9a+9y= | | 6k=3.2 | | 100x=60x+(180-X)*10 | | x(2x-5)=(2x+6)(x-4) | | 2(3-4x)=2(2x+1) | | 6y-7=14y+25 | | 7-4k=1 | | 6x-9=2x-81 | | 5y=x+20 | | -2(1-2x)-(1-2x)=-x-2 | | -10+8+(-4)= | | 6*(2B-3)=18 | | -14+6x=3 | | lny=2x^2+C | | 4*(5A+1)=24 | | 9x-(3x+11)=43 | | 61-(-23)+21-40= | | 9(4x-3)=50 | | 13-8x=-75 | | 9m-4(2m-4)=12 | | h+1100+l=57400 | | -13+11= |